2011
DOI: 10.1002/lsm.21077
|View full text |Cite
|
Sign up to set email alerts
|

Laser reshaping of costal cartilage for transplantation

Abstract: It is possible to use laser reshaping technique for preparation of stable cartilage implants. Nonlinear thermomechanical behavior of cartilage is experimentally revealed. The influence of irradiation sequence on curvature radius of cartilage grafts is established for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 15 publications
(21 reference statements)
2
52
0
3
Order By: Relevance
“…The creation of long‐term stable thermo‐mechanical deformation of cartilaginous tissues has already been demonstrated in laser‐induced reshaping of nasal septum, with stable results on a scale of several years ; by now hundreds of patients have passed through such non‐surgical laser‐assisted operations. Similar stable results have been obtained with reshaping of excised planar pieces of costal cartilage into circular implants for surgical operations on trachea; these implants also demonstrate stability of the acquired shape, provided the internal stresses are sufficiently relaxed due to laser‐induced heating . Similarity in the chemical composition and thermo‐mechanical behavior between cornea and cartilages suggests that the reshaped cornea should also demonstrate long‐term shape stability.…”
Section: Discussionsupporting
confidence: 62%
“…The creation of long‐term stable thermo‐mechanical deformation of cartilaginous tissues has already been demonstrated in laser‐induced reshaping of nasal septum, with stable results on a scale of several years ; by now hundreds of patients have passed through such non‐surgical laser‐assisted operations. Similar stable results have been obtained with reshaping of excised planar pieces of costal cartilage into circular implants for surgical operations on trachea; these implants also demonstrate stability of the acquired shape, provided the internal stresses are sufficiently relaxed due to laser‐induced heating . Similarity in the chemical composition and thermo‐mechanical behavior between cornea and cartilages suggests that the reshaped cornea should also demonstrate long‐term shape stability.…”
Section: Discussionsupporting
confidence: 62%
“…Laser‐induced modification of cartilaginous tissue for medical applications uses the moderate energy modes when the tissue is heated on tens of degrees for short times below the thresholds of thermal alterations of the tissue components . In some cases like cartilage reshaping the needed temperature for stress relaxation may exceed the equilibrium denaturation temperature, however, at short pulses the tissue cooling is much faster than the phase transformation has time to occur.…”
Section: Resultsmentioning
confidence: 99%
“…A perspective technology of infrared (IR) laser reshaping of cartilage in larynx stenosis surgery implies the usage of autologous costal cartilage implants to be extracted from the patient rib, irradiated to obtain stable semicircle shape and implanted to cover the trachea defect during a single operation procedure . IR laser‐induced temperature of around 70 °C is the critical parameter needed for effective relaxation of internal mechanical stress and obtaining of a new shape .…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the obtained effect for implants of different thickness we showed that well‐controlled heating through the whole thickness of an implant is crucial for the new shape stability . Simultaneously, the very local heating of cartilage by separate laser spots is needed to avoid thermal injury of matrix and cells . But the attempts to heat the deep tissue layers of thicker implants may cause the superficial burn and substantially disturb the safety of the procedure.…”
Section: Introductionmentioning
confidence: 99%